Accuracy and Reliability of The Visual Assessment of Patellar Tracking. Issue 3 (31st March 2019) - Best, Matthew; Tanaka, Miho Jean; Demehri, Shadpour; Cosgarea, Andrew J.
Objectives: Clinicians treating patients with patellar instability describe abnormal tracking as a "J sign" when the patella exhibits excessive lateral displacement as the knee is actively extended. The purpose of this study is to determine the accuracy and reliability of the visual assessment of patellar tracking among patellofemoral experts when compared to objective radiographic measurements. Methods: Active knee extension was video recorded and a dynamic CT scan (4D CT) was obtained in study patients being evaluated for patellar instability. Patellar bisect offset (BO) was measured directly from the 4D CT at 10-degree increments from 0-50 degrees of flexion. The greatest BO value was used to determine quadrants of lateral translation. Practicing orthopedic surgeons from the International Patellofemoral Study Group (IPSG) were asked to view videos and determine the presence or absence of maltracking (2 or more quadrants of lateral translation) in 10 single-knee videos (qualitative analysis). Participants were then asked to grade patella tracking in 20 different single-knee videos (quantitative analysis). J-sign grade was defined as follows: grade 0 - less than 1 patellar quadrant of lateral translation; grade 1 - at least 1 but less than 2 quadrants; grade 2 - at least 2 but less than 3 quadrants; grade 3 - 3 or more quadrants lateral translation. Results: Thirty-two practicing orthopedic surgeon IPSG members completed the survey. In the qualitative analysis, the videos were correctly identified as demonstrating patellar maltracking 68% of the time (free marginal kappa= 0.44). In the quantitative analysis, 53% of survey participants identified grade 3 J sign correctly, 51% correctly identified grade 2, 48% correctly identified grade 1, and 68% correctly identified grade 0 (free marginal kappa= 0.42). Conclusion: This is the first study to compare visual assessment of patellar tracking with objective BO measurements from 4D CT. Using visual assessment alone, patellofemoral experts were able to correctly identify the presence of patellar maltracking in only two-thirds of the videos and were able to correctly grade patellar maltracking in only half. There is inadequate interobserver agreement (free marginal kappa<0.70) to support the use visual assessment alone in determining the presence or degree of patellar maltracking, reinforcing the importance of objective radiographic measurements.